2017
DOI: 10.1038/s41598-017-08034-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long working hours and periodontitis among the Korean workers

Abstract: We aimed to investigate the association between long working hours and periodontitis, and whether such an association constitutes an exposure-response relationship. Data for this study were collected from the Korea National Health and Nutrition Examination Surveys conducted from 2007 to 2014; 17,533 workers (9,483 of men and 8,050 of women) were included. The odds ratios (OR) and 95% confidence intervals (CI) for the analysis of periodontitis defined as positive of Community Periodontal Index in relation to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
0
17
1
2
Order By: Relevance
“…In the present study, no significant difference in overtime work was found between the periodontitis and non-periodontitis groups. A previous study among Korean workers reported that overtime work was associated with the prevalence of periodontitis [40]. The discrepancy in the findings from the previous study and the present study may depend on race (Korean vs. Japanese) and the percentage of overtime workers (60.3% vs. 25.3%).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In the present study, no significant difference in overtime work was found between the periodontitis and non-periodontitis groups. A previous study among Korean workers reported that overtime work was associated with the prevalence of periodontitis [40]. The discrepancy in the findings from the previous study and the present study may depend on race (Korean vs. Japanese) and the percentage of overtime workers (60.3% vs. 25.3%).…”
Section: Discussioncontrasting
confidence: 96%
“…Therefore, the influence of stress and coping style on periodontitis might differ from other types of workers. Second, no other possible confounders, such as working schedule [40], education level [3], income level [47], and family situation [48], were examined in this study. Third, periodontitis was diagnosed using an objective method due to time constraints, but no probing or X-ray findings were used.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, health check-ups in the hospital, including oral examinations, are popular. In addition, it is accepted that having probing pocket depth (PPD) ≥4 mm indicates that the individual has periodontal disease 15 . Therefore, the purpose of this cross-sectional study was to investigate the relationship between NAFLD and having PPD ≥4 mm in a Japanese oral health check population.…”
Section: Introductionmentioning
confidence: 99%
“…Some occupational factors, such as overtime work [ 9 ] and shift work [ 22 ], have been reported to increase the morbidity of dental diseases (e.g., periodontal disease); however, the direct cause has not yet been established. Preventive dental visits reduce the risk for caries and periodontal disease and have an important role in oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent tooth loss is associated with a reduction in intraoral function, and an increased risk for depression and cognitive decline [ 5 , 6 ]. In addition, periodontitis has been identified as a risk factor for systemic diseases such as diabetes and coronary heart disease [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%